Umbilical cord bloods hematopoietic stem cells ex vivo expansion (the literature review) - T. V. Shamanskaya; E. Yu. Osipova; S. A. Roumiantsev (Онкогематология, 2014)
Umbilical cord blood (CB) is now an attractive source of hematopoietic stem cells (HSCs) for transplantation in pediatric and adult patients with various malignant and non-malignant diseases. However, its clinical application is limited by low cells numbers in graft, which correlates with delayed engraftment, an extension of time to platelets and neutrophils recovery and increasing risk of infectious complications. Several strategies have been suggested to overcome this limitation, one of which is obtaining a sufficient number of hematopoietic progenitor cells by ex vivo expansion. Literature review about CB HSCs expansion in given article is presented.